Combining cooperativity with sequestration: a novel strategy for discrimination of single nucleotide variants. Issue 26 (12th March 2018) - Hu, Shichao; Li, Na; Liu, Feng
Abstract : We present a novel single nucleotide variant discrimination strategy combining cooperativity with sequestration to significantly improve the discrimination ability. Abstract : We present a novel strategy for the discrimination of single nucleotide variants (SNVs) by combining cooperativity with sequestration, which displays remarkably high specificity (discrimination factors ranging from 67 to 618 with a median of 194) against 12 model SNVs and can be easily integrated with PCR amplification to detect KRAS G12D mutation.